Formation of bio-based cyclic carbonates from CO2 and renewable feedstocks via porous poly(azomethine) -based heterogeneous catalysts approach - Marcelo Echeverri; Eva M. Maya; Dulce M. Muñoz (Journal of CO2 Utilization)
Two families of heterogeneous porous catalysts based on iron or cobalt poly(azomethine) (PAM) networks were reported to synthesize cyclic carbonates from bio-based aliphatic oxides epoxides and carbon dioxide (CO2). The different PAM supports were prepared by reacting 2,6-pyridine dicarboxaldehyde with 1,3,5 tris(4 aminophenyl)benzene (PAM-1) or with melamine (PAM-2) by microwave activation. Both supports exhibited high thermal stability and similar CO2 uptake (1.3 mmol/g) but PAM-2 showed higher specific surface area (779 m2/g vs 401 m2/g), more crystallinity and less capacity for anchoring metals than PAM-1. The novel catalysts were used in the cycloaddition of CO2 to renewable feedstocks. Thus, using epoxidized methyl oleate (MOE) the corresponding cyclic carbonates were obtained with excellent yields (78–96 %) using a CO2 pressure of 7 bars, 120 ºC and 16 h of reaction. The best catalysts of the series, Fe@PAMs were also evaluated in the cycloaddition of CO2 to epoxidized soybean oil (ESBO) in the same condition reaction obtaining excellent performance, epoxide conversions and cyclic carbonate yields greater than 90 %.